2007
DOI: 10.1007/s11144-007-4975-x
|View full text |Cite
|
Sign up to set email alerts
|

Recycle and recovery of rhodium complexes with water-soluble and amphiphilic phosphines in ionic liquids for hydroformylation of 1-hexene

Abstract: A biphasic catalysis system composed of ionic liquid and rhodium complexes with water-soluble or amphiphilic phosphine ligands bearing water-soluble groups of sodium sulfonate have been employed for hydroformylation of 1-hexene. The experimental results show that the activity is almost independent of the hydrotropicity of the phosphine ligands in BMI center dot BF4. In this system, the extraction of phosphine species by the organics from the IL phase was quite low but larger than that of rhodium species and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Another example can be found in the pioneering work of Chauvin et al, who used TPPMS - and PPh 3 as ligands in conjunction with [BMI][PF 6 ] as the IL: 12 neutral ligands lead to high conversion rates and to important leaching of the catalyst, which is consistent with a reaction mainly occurring in the organic phase. Our results at the interface are consistent with Peng et al's observation of an increase of the hydroformylation efficiency when using amphiphilic ligands, in both classical water−oil and IL−oil binary systems . They found that with [BMI][PF 6 ] as the IL, the reaction was favored with (i) −1 charged ligands as compared to −2 and −3 charged ones and (ii) when the aryl rings of the phosphine ligands become substituted by a t -Bu group, thereby becoming more amphiphilic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another example can be found in the pioneering work of Chauvin et al, who used TPPMS - and PPh 3 as ligands in conjunction with [BMI][PF 6 ] as the IL: 12 neutral ligands lead to high conversion rates and to important leaching of the catalyst, which is consistent with a reaction mainly occurring in the organic phase. Our results at the interface are consistent with Peng et al's observation of an increase of the hydroformylation efficiency when using amphiphilic ligands, in both classical water−oil and IL−oil binary systems . They found that with [BMI][PF 6 ] as the IL, the reaction was favored with (i) −1 charged ligands as compared to −2 and −3 charged ones and (ii) when the aryl rings of the phosphine ligands become substituted by a t -Bu group, thereby becoming more amphiphilic.…”
Section: Discussionsupporting
confidence: 91%
“…Our results at the interface are consistent with Peng et al's observation of an increase of the hydroformylation efficiency when using amphiphilic ligands, in both classical water-oil 78 and IL-oil binary systems. 79 They found that with [BMI][PF 6 ] as the IL, the reaction was favored with (i) -1 charged ligands as compared to -2 and -3 charged ones and (ii) when the aryl rings of the phosphine ligands become substituted by a t-Bu group, thereby becoming more amphiphilic.…”
Section: Discussionmentioning
confidence: 99%
“…36,37,[41][42][43][44][45][46][47] Several groups have reported phosphine and phosphite based FILs as hydroformylation ligands that improve the solubility of higher alkene reactants in the catalytic phase, while simultaneously improving catalyst retention and selectivity. 33,35,42,45,46,[48][49][50][51][52][53][54] In the context of IL-stabilized transition metal nanoparticles (NPs), [55][56][57][58][59][60][61][62][63][64][65] our group and others have studied the influence of changing the parameters of FILs (i.e. alkyl chain length, counter anion) on the catalytic properties of transition metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Favre et al found that the problem of Rh leaching could be minimized by the modification of phosphorus ligands with cationic (guanidinium or pyridinium) or anionic (sulfonate) groups [22]. An easy phase separation has been reported to be viable between the reactants-containing organic phase and the water-soluble phosphine-Rh complexes-containing ionic liquid phase after the hydroformylation [23][24][25][26][27][28]. We have been working for years on the synthesis and catalytic properties of phosphine ligands for hydroformylation with aqueous biphasic, ionic liquid biphasic and for supported catalysts [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…An easy phase separation has been reported to be viable between the reactants-containing organic phase and the water-soluble phosphine-Rh complexes-containing ionic liquid phase after the hydroformylation [23][24][25][26][27][28]. We have been working for years on the synthesis and catalytic properties of phosphine ligands for hydroformylation with aqueous biphasic, ionic liquid biphasic and for supported catalysts [27][28][29][30][31][32][33][34][35]. Herein the chiral bidentate phosphine ligand (R)-2,2 -bis(diphenylphosphino)-1,1 -binaphthyl (i.e., (R)-BINAP), which is conveniently available in the enantio-pure form, was used as chiral model ligand since it was already known to induce enantio-selectivity in several hydroformylation [4,36] and also the ruthenium (Ru) complexes of (R)-BINAP are excellent catalysts for asymmetric hydrogenation [37].…”
Section: Introductionmentioning
confidence: 99%